Developing the right to education in the context of regional African human rights law : protecting children with non-heteronormative sexual orientations, non-binary gender identities or gender expressions - Kreuser, Charlene (Stellenbosch : Stellenbosch University, 2021)
Thesis (LLD)--Stellenbosch University, 2021.